EVALUATION OF THE EFFICACY OF CERAMIC POSTS USED IN THE RESTORATION OF CORONAL PORTION DEFECTS OF TEETH (International journal of medical sciences, 2026)
This article investigates the clinical, biomechanical, and economic aspects of using milled ceramic post-and-cores in the orthopedic restoration of teeth with substantial hard tissue loss resulting from caries complications. The study provides a comparative analysis of ceramic and metal post-and-cores concerning biocompatibility, aesthetic parameters, load distribution, and labor intensity. The obtained results indicate that milled ceramic post-and-cores are a promising option for clinical practice.